Who Moves and For How Long: Determinants of Different Forms of Migration - Daniela Borodak; Matloob Piracha (Institute for the Study of Labor (IZA), 2013)
This paper analyses the determinants and correlates of different forms of migration, including circular, temporary and permanent. Using Moldovan data we show that age, education, number of children in a household and social as well as economic development in the region of origin play a crucial role in the decision to migrate permanently or on temporary/circular basis. We believe that understanding who moves and whether temporarily or circularly will help formulate more effective migration policies both in the sending and receiving countries.
Keywords: C35; F22; J61; 330; circular migration; return migration; nested logit; Moldova